PENGARUH LIKUIDITAS LEVERAGE DAN PROFITABILITAS TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2011-2015 - Maya Dewi Suprobo; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2017)
Abstract This research purposed to analyze the effect of liquidity (current ratio), leverage (debt to asset ratio) and profitability (return on assets) to financial distress on transportation company listed in Indonesia Stock Exchange (IDX) 2011-2015. This research data used secondary data that getting from financial report of transportation company listed in Indonesia Stock Exchange (BEI). The total of sample 110 transportation company. The method of research is logistic regression with the program SPSS 14. The results of this research showed that regression coefficient of current ratio variable was -0,295; regression coeffisient of debt to asset ratio was 3,086 and; regression coefficient return on assets variabel was -1,988, it means liquidity ratio (current ratio) and profitability (return on assets) negatively affected to condition of company financial distress and leverage ratio positively affected to condition of company financial distress.Keywords: liquidity (current ratio), leverage (debt to asset ratio) profitability(return on asset), financial distress